Development of Geogedu Game on Curved Shapes to Improve Conceptual Understanding and Spatial Ability - Kurniawati, Yeva -; Lutfiah, Nour Aisyah (International Journal on Teaching and Learning Mathematics, 2025)
This study aims to determine the validity, practicality, and effectiveness of Geogedu, an educational game designed to enhance students’ conceptual understanding and spatial abilities. The development of Geogedu was driven by the need for innovative media to address students’ difficulties in visualizing spatial concepts and curved shapes. Developed using MIT App Inventor, Geogedu integrates interactive features to support engaging learning. The development process followed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). In the Development phase, expert validation resulted in a score of 3.2 (quite valid), and a limited trial assessed usability and functionality. During the Implementation phase, Geogedu was tested on 35 students of Grade IX at SMP BP Maarif Assaadah to evaluate its practical use in a real classroom setting. The practicality score was 3.45 (practical), and the N-gain score was 0.45, indicating medium effectiveness. These findings suggest that Geogedu is a valid, practical, and moderately effective learning media that can be used in classroom instruction to improve students’ conceptual understanding and spatial abilities.